Treatment response evaluation with 18F-FDG PET/CT and 18F-NaF PET/CT in multiple myeloma patients undergoing high-dose chemotherapy and autologous stem cell transplantation - Sachpekidis, Christos; Hillengaß, Jens; Goldschmidt, Hartmut; Wagner, Barbara; Haberkorn, Uwe; Kopka, Klaus; Dimitrakopoulou-Strauss, Antonia (European journal of nuclear medicine and molecular imaging, 2017)
AIM: The aim of this study was to assess the combined use of the radiotracers 18F-FDG and 18F-NaF in treatment response evaluation of a group of multiple myeloma (MM) patients undergoing high-dose chemotherapy (HDT) followed by autologous stem cell transplantation (ASCT) by means of static (whole-body) and dynamic PET/CT (dPET/CT). PATIENTS AND METHODS: Thirty-four patients with primary, previously untreated MM scheduled for treatment with HDT followed by ASCT were enrolled in the study. All patients underwent PET/CT scanning with 18F-FDG and 18F-NaF before and after therapy. Treatment response by means of PET/CT was assessed according to the European Organization for Research and Treatment of Cancer (EORTC) 1999 criteria. The evaluation of dPET/CT studies was based on qualitative evaluation, semi-quantitative (SUV) calculation, and quantitative analysis based on two-tissue compartment modelling and a non-compartmental approach leading to the extraction of fractal dimension (FD). RESULTS: An analysis was possible in 29 patients: three with clinical complete response (CR) and 26 with non-CR (13 patients near complete response-nCR, four patients very good partial response-VGPR, nine patients partial response-PR). After treatment, 18F-FDG PET/CT was negative in 14/29 patients and positive in 15/29 patients, showing a sensitivity of 57.5 % and a specificity of 100 %. According to the EORTC 1999 criteria, 18F-FDG PET/CT-based treatment response revealed CR in 14 patients (18F-FDG PET/CT CR), PR in 11 patients (18F-FDG PET/CT PR) and progressive disease in four patients (18F-FDG PET/CT PD). In terms of 18F-NaF PET/CT, 4/29 patients (13.8 %) had a negative baseline scan, thus failed to depict MM. Regarding the patients for which a direct lesion-to-lesion comparison was feasible, 18F-NaF PET/CT depicted 56 of the 129 18F-FDG positive lesions (43 %). Follow-up 18F-NaF PET/CT showed persistence of 81.5 % of the baseline 18F-NaF positive MM lesions after treatment, despite the fact that 64.7 % of them had turned to 18F-FDG negative. Treatment response according to 18F-NaF PET/CT revealed CR in one patient (18F-NaF PET/CT CR), PR in five patients (18F-NaF PET/CT PR), SD in 12 patients (18F-NaF PET/CT SD), and PD in seven patients (18F-NaF PET/CT PD). Dynamic 18F-FDG and 18F-NaF PET/CT studies showed that SUVaverage, SUVmax, as well as the kinetic parameters K1, influx and FD from reference bone marrow and skeleton responded to therapy with a significant decrease (p < 0.001). CONCLUSION: F-FDG PET/CT demonstrated a sensitivity of 57.7 % and a specificity of 100 % in treatment response evaluation of MM. Despite its limited sensitivity, the performance of 18F-FDG PET/CT was satisfactory, given that 6/9 false negative patients in follow-up scans (66.7 %) were clinically characterized as nCR, a disease stage with very low tumor mass. On the other hand, 18F-NaF PET/CT does not seem to add significantly to 18F-FDG PET/CT in treatment response evaluation of MM patients undergoing HDT and ASCT, at least shortly after therapy.
First online: 29 August 2016
Gesehen am 05.06.2018